Alexander Hamilton - Chernow, Ron (Penguin Books, 2005)
Chernow "vividly re-creates the whole sweep of Hamilton's turbulent life-- his exotic, brutal upbringing; his titanic feuds with celebrated rivals; his pivotal role in defining the shape of the Federal government; his shocking illicit romances; his enlightened abolitionism; and his famous death in a duel with Aaron Burr in July 1804. Drawing upon extensive, unparalleled research-- including nearly fifty previously undiscovered essays highlighting Hamilton's fiery journalism as well as his revealing missives to colleagues and friends.-- this biography of the extraordinarily gifted founding father who galvanized, inspired, and scandalized the newborn nation is the work by which all others will be measured"--